Defect‐Mediated Anisotropic Lattice Expansion in Ceramics as Evidence for Nonthermal Coupling between Electromagnetic Fields and Matter. Issue 12 (26th September 2019) - Jha, Shikhar Krishn; Nakamura, Nathan; Zhang, Shuyan; Su, Laisuo; Smith, Phil M.; Phuah, Xin L.; Wang, Han; Wang, Haiyan; Okasinski, John S.; McGaughey, Alan J. H.; Reeja-Jayan, B.
Abstract : Electromagnetic (EM) fields can trigger a range of surprising responses in materials. Microwave radiation (MWR), a type of EM field in the frequency range of 0.3–300 GHz, can lower the synthesis temperature required for ceramics such as TiO2 and induces mixed amorphous–crystalline phase compositions. To better understand the effects of MWR on matter, structural changes during microwave heating and MWR‐assisted synthesis using in situ synchrotron X‐ray diffraction are studied. Anisotropic expansion–contraction of lattice parameters under microwave‐radiation is observed, which contradicts the results from conventional thermal heating. When as‐received TiO2 powders are heated with MWR, an instantaneous decrease in the intensities of diffraction peaks indicates decrystallization/amorphization. High‐resolution electron microscopy supports these observations. Raman spectroscopy and X‐ray photoemission spectroscopy indicate increased defect‐generation under microwave exposure. Molecular dynamics simulations on the anatase phase of TiO2 suggests that introducing an oxygen vacancy can lead to the formation of an interstitial–vacancy pair resulting in anisotropic expansion–contraction of the lattice. These unique responses of ceramics under externally applied fields provide direct evidence for nonthermal coupling between EM fields and matter. Understanding such nonthermal, field‐driven processes has implications in engineering low‐temperature processes for integrating ceramics with polymers for flexible electronics, energy harnessing, and storage applications. Abstract : Microwave radiation couples directly with the matter by nucleating defects in the lattice structure, beyond their thermal equilibrium. Lattice defects induce decrystallization (ordered–disordered phase transformation) and abnormal lattice expansion. This nonthermal effect of external fields is suggested to be the reason for lowering down of processing time and temperature under microwave‐assisted processing.